(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Vildagliptin is an oral hypoglycemic agent used in the management of diabetes. Some oral antidiabetic drugs have been implicated in reproductive toxicity.The objective of this study was to investigate the effects of daily administration of vildagliptin at different dosages (0.35 mg/kg B.W., 0.70 mg/kg B.W. and 1.40 mg/kg B.W.) to male Wistar rats for 8 weeks. Sperm parameters, serum concentrations of testosterone, follicle stimulating hormone and luteinizing hormone and the histology of the testis of the rats were assessed. Another set of rats were also treated for 8 weeks and allowed to recover and the same parameters were assessed in them. Fertility study was conducted by determining their litter size. The results showed that vildagliptin administration significantly reduced sperm count and motility of the treated rats. It also significantly increased the number of abnormal sperms. Serum level of testosterone was significantly decreased while luteinizing hormone and follicle stimulating hormone levels showed no significant change. The histoarchitecture of the testis of the treated rats appeared visibly normal. The litter size was also significantly reduced. Most of the changes observed were dose dependent. However, these parameters were restored towards normal in the recovery group. Our results suggest that vildagliptin adversely affected sperm parameters, affected litter size and disrupted the pituitary – gonadal axis. These changes were however reversed upon cessation of drug administration.